Macroeconomics policy and practice - Mishkin, Frederic S. (Pearson Education Limited, 2015)
Building on his expertise in macroeconomic policymaking at the Federal Reserve, Mishkin's text clearly provides a theoretical framework that illustrates the most current and relevant policy debates in the field